Persuasive Communication Strategy in Creative Work Digital Marketing Agency : Descriptive Study of Creative Works Digital Marketing Agency - Wijaya, Adel Lia Iralda (CV. Publikasi Indonesia, 2024)
The pandemic period in recent years has made it difficult for business people and MSMEs to market their products. This is one of the reasons for the establishment of the digital agency Karya Creative. This research also focuses on how Karya Creative's persuasive communication strategy to attract prospective clients to entrust their brand and what are the factors that influence the success of persuasive communication by Karya Creative in attracting clients. In this research, researchers took an approach used in qualitative descriptive. In using qualitative descriptive type, where researchers describe or construct in-depth interviews of research subjects. The results of this study show the process of persuasive communication strategies applied in Creative Works, the elements and components of persuasive communication used, and what factors influence the success of persuasive communication of Creative Works. Researchers hope that this research can make a scientific contribution to communication science and be useful for students who pursue communication research. The advice obtained from this study is that persuasive communication must be given continuously to convince clients because it is the basis of the strength of marketing agencies in promoting. Then it is also important in building client trust, of course, we need to uphold an honesty or a transparent communication.